One new species of Xizicus in the genus subgenus Paraxizicus (Orthoptera: Tettigoniidae: Meconematinae) from Yunnan Province, China - Zhang, Qianwen; Bian, Xun (Zootaxa, 2023)
This paper describes one new species of the genus Xizicus (in subgenus Paraxizicus) from Yunnan Province, China, which can be distinguished by the shapes of the median process of male tenth abdominal tergite, cerci and subgenital plate. Based on the specimen deposited in Guangxi Normal University, the illustrations of the new species are provided.